Beyond the Motor Cortex: Thalamic Iron Deposition Accounts for Disease Severity in Amyotrophic Lateral Sclerosis - Li, Qianwen; Zhu, Wenjia; Wen, Xinmei; Zang, Zhenxiang; Da, Yuwei; Lu, Jie (Frontiers in Neurology, 2022)
Objective Previous studies have reliably identified iron deposition in the motor cortex as a potential pathogenesis of amyotrophic lateral sclerosis (ALS). Here, we intended to investigate iron deposition, grey matter (GM) atrophy and their associations with disease severity in the motor cortex and the thalamus in ALS patients. Methods Thirty-four ALS patients (age 51.31 ± 8.24, 23 males) and 34 non-neurological controls (age 50.96 ± 9.35, 19 males) were enrolled between 2018 and 2020. The revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) and the Penn Upper Motor Neuron (UMN) score were measured. Magnetic resonance imaging (MRI) data included quantitative susceptibility mapping (QSM) for iron deposition and 3D T1 for gray matter volume. After between-group comparison, Pearson’s correlation was used for identifying correlations of iron deposition, GM volume and clinical measurements. Results Two-sample T tests revealed increased iron deposition in the left precentral gyrus (peak voxel T = 4.78, PSVC = .03) and the thalamus (peak voxel: right: T = 6.38, PSVC < .001; left: T = 4.64, PSVC = .02) in ALS patients. GM volume of the precentral gyrus (T = -2.42, P = .02) and the bilateral thalamus (T = -4.10, P < .001) were reduced. Negative correlations were found between the increased QSM values and the decreased GM volume (P values < .04, one-tailed) in ALS patients. Iron deposition in the left precentral gyrus was positively correlated with the UMN score (R = 0.40, P = .02) and the GM volume was negatively correlated with the UMN score (R = -0.48, P = .004). Negative correlation between thalamic iron deposition and the ALSFRS-R (R = -0.36, P = .04) score was observed. Discussion Iron deposition in the thalamus in addition to the motor cortex is accompanied with GM atrophy and associated with disease severity in the ALS patients, indicating that the thalamus is also a pathological region in ALS patients.